Observations of spontaneous cherubism based on two cases and a literature review - Brodowski, Robert; Pakla, Paweł; Myszka, Aleksander; Czenczek-Lewandowska, Ewelina; Bałuszyński, Michał; Lewandowski, Bogumił (Medical Studies/Studia Medyczne, 2023)
Cherubism is a genetically determined illness characterized by osseus lesions of the facial part of the skull. X-ray and histopathological analysis of cherubism show it to be similar to fibrosis dysplasia, a brown tumour that occurs in the parathyroids or giant cells. Our paper describes 2 cases of cherubism. In each of them, X-ray examination, histopathological analysis and genetic tests led to a diagnosis. In this study, in the first case, there was no mutation in the SH3BP2 gene, which does not exclude the possibility that the mutation occurs in another gene. In the second case, in a patient diagnosed with cherubism after many years of observation and when clinical symptoms had worsened, genetic tests confirmed a mutation in exon 9 of the SH3BP2 gene.